Analisis Laju Dosis Radiasi di Area Ruang CT_Scan di Instalasi Radiologi RSU Bali Mandara - Prameswari, Else Putri Ayu; Sutapa, Gusti Ngurah; Ayu Ratnawati, I Gusti Agung; Ratini, Ni Nyoman; Artawan, I Nengah; Trisnawati, Ni Luh Putu (Kappa Journal, 2024)
Research has been carried out on radiation dose rate analysis in the CT-SCAN area of the radiology room at RSU Mandara Bali. The data used in this research is quantitative data observed from the radiation rate from the CT-SCAN aircraft. This study aims to determine the radiation dose rate in the radiology area and its rationalization based on regulations regarding radiation NBD (dose limit values) that apply to occupational safety and health. The research data is the actual radiation dose rate determined from the dose rate and calibration factors. The results of data calculations show that the highest dose rates are respectively at T2, 30 cm, 50 cm and 100 cm (door) with values of 1.95, 0.94 and 0.05 μSv/year, while the lowest dose rates are respectively at T4, 30 cm, 50 cm and 100 cm (waiting room) with values of 0.08, 0.06 and 0.05 μSv/year. The research results show that the dose rate at each measurement point is still considered safe for radiation workers where the NBD received is still below 20 μSv/year, while the dose rate is classified as safe for the general public at measuring distances of 50 cm and 100 cm, where the NBD received is below 1 μSv/year assuming the community concerned acts as a patient or patient's family with an interest in the radiology room area.